Proximate, Mineral Contents and Physicochemical Properties of Chrysophyllum Albidum (African Star Apple) Kernel Flour and Oil - S.S. Audu; C.I. Beetseh; D.U. Edward-Ekpu; A.A. Ewuga (Journal of Applied Sciences and Environmental Management)
The flour and oil of the kernel of African Star Apple (Chrysophyllum Albidum Linn.) sourced from Maraba Gurku township of Nasarawa state was analysed to determine their potentials for industrial and human consumption. Standards methods were used to determine the proximate and mineral contents of the flour and physicochemical properties of the oil. The results obtained from the Proximate Analysis shows the kernel has a moisture content of 10.06±0.08 %, Ash content of 2.72±007 %, Crude lipid of 13.31±008 %, Crude Protein of 7.92±0.00 %, Crude Fibre of 1.59±0.00 % and Carbohydrate of 65.41±0.05 %. This suggests that the flour can be a used as an alternative to cereals in compounding animal feed. The results from the Mineral Analysis showed the kernel has 0.01 mg/g of copper, 0.01 mg/g of Iron, 37.50 mg/g of phosphorus, 57.37 mg/g of calcium and 0.44 mg/g magnesium. The Calcium-Potassium Ratio indicates the flour is a good source of calcium for bone formation. The Physicochemical analysis showed the oil has an Acid Value of 33.12±0.25 mgKOH/g, a Saponification Value of 184.90±0.29 mgKOH/g, an Iodine Value of 60.05±0.02 mgKOH/g, a Free Fatty Acid Value of 16.05±0.14 mgKOH/g, Peroxide Value of 2.10±0.10 m Eq/kg, Moisture of 3.36±0.08 %, Unsaponifiable Matter of 5.26±0.05 g/kg and an Ester Value of 151.78±0.15 mgKOH/g. The quality of the kernel oil falls below the standard for edible oil but the oil may be useful in the paint and cosmetic industry